Impulsive buying behavior depending on gender - Nicolae Istudor; Corina Pelau (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
One of the biggest challenges of companies is to determine the behavior of its consumers, because only by this it can influence determine them to buy their products. It is not enough just to know the behavior of the consumer at one moment of time, but also its dynamic. On one hand there are changes at the level of each individual when passing from one stage of his life to another, and on the other hand, there are also changes determined by the society such as changes in values and norms, trends, technological developments. For this reason in consumer behavior it is important to analyze this dynamic and try to find the reasons for these changes, because only by this a company can adjust its products and strategies. This article presents several aspects of the Romanian consumer behavior, depending on age and gender. There are analyzed for different segments of population patterns of consumer behavior, the social and emotional behavior, the impulsive buying behavior and the attitude of the consumer towards this type of behavior
Keywords: 650; consumer behavior; consumer segments; consumer typologies